Reconstitution of the complete pathway of ITS2 processing at the pre-ribosome - Fromm, Lisa; Flemming, Dirk; Thoms, Matthias; Hurt, Ed (Nature Communications, 2017)
Excision of internal transcribed spacer 2 (ITS2) within eukaryotic pre-ribosomal RNA is essential for ribosome function. Here, the authors reconstitute the entire cycle of ITS2 processing in vitro using purified components, providing insights into the cleavage process and demonstrating that 26S pre-rRNA processing necessarily precedes 7S pre-rRNA processing.